2022
DOI: 10.5334/irsp.682
|View full text |Cite
|
Sign up to set email alerts
|

“Sorry for what we did”: A Social Psychological Understanding of Political and Intergroup Apologies (Introduction to the Special Issue)

Abstract: Research on political apologies spans sociopolitical contexts and disciplines and methodological frameworks. In the rise of interest in political apologies, especially in light of 'the age of apologies', social psychologists strive to understand mechanisms of issuing, perception and evaluation of political apologies from many perspectives. This special issue aims to highlight the important role of social psychological theory in understanding political apologies and deepening knowledge in this field. The papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Policy-makers may benefit from such empirical evidence, on the grounds that transgressions occur worldwide increasing, in turn, the need for effective and convincing modes of political communication, restoration of trust and reassurance of reparative actions. It is worth acknowledging that we live 'in the age of apologies' (Gkinopoulos et al, 2022) and the need for robust experimental evidence of perceptions and evaluations of political apology forms in real-life transgressions is more urgent and informative than ever. Such evidence helps social psychologists and other political scientists understand underlying mechanisms that determine the effectiveness of one or another political apology form.…”
Section: General Discussion Limitations and Future Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Policy-makers may benefit from such empirical evidence, on the grounds that transgressions occur worldwide increasing, in turn, the need for effective and convincing modes of political communication, restoration of trust and reassurance of reparative actions. It is worth acknowledging that we live 'in the age of apologies' (Gkinopoulos et al, 2022) and the need for robust experimental evidence of perceptions and evaluations of political apology forms in real-life transgressions is more urgent and informative than ever. Such evidence helps social psychologists and other political scientists understand underlying mechanisms that determine the effectiveness of one or another political apology form.…”
Section: General Discussion Limitations and Future Directionsmentioning
confidence: 99%
“…Attwood, 2008;Slocum et al, 2011) confirmed the higher perceived sincerity, trust and forgiveness of offenders in the self-other apology than in self-focus apology. However, emphasis was still given on the wording of apologies (Berndsen et al, 2015;Gkinopoulos et al, 2022), that is the way that political apologies are rhetorically framed and the word content of those apologies rather than the setting they took place or the interlocutors involved in them.…”
Section: Self-focused and Self-other Focused Apologies: The Staircase...mentioning
confidence: 99%
See 3 more Smart Citations